Efeitos de três programas de fisioterapia respiratória em portadores de DPOC - Kunikoshita, Luciana Noemi (2006)
The aim of the present study was to evaluate the effects of three respiratory physiotherapy programs constituted by physical training (PT) on a treadmill and/or respiratory muscle training (RMT) on pulmonary function, respiratory muscle strength (RMS), quality of life (QL), exercise capacity, ventilatory and metabolic variables and dyspnea at rest and during exercise, in patients with COPD, as well as to compare them to subjects of the same age and who have no respiratory disease. Twenty-five patients (68.8±8.3 years old) of both sexes, with moderate-to-severe COPD (FEV1<60% predicted), and ten volunteers who have no respiratory disease of both sexes (67.2±7.4 years old) participated of this study. The patients with COPD were randomized into three groups: the first group (RMTG) underwent 20 minutes sessions of RMT at a resistive load corresponding to 30% of the MIP obtained each week; the second group (PTG) underwent 30 minutes sessions of PT at a work rate corresponding to 70% of the highest heart rate achieved in the symptom-limited cardiorespiratory exercise testing (CRET); and the third group (RMT+PTG) associated 10 minutes of RMT to 15 minutes of PT with the same intensities previously mentioned. All of the programs were constituted by three sessions per week during six consecutive weeks. After treatment, it was observed significant increase of MIP and MEP in RMTG; significant increase of walk distance (WD) in the CRET, decreases of HR and minute ventilation at the same velocity in the CRET after treatment and improvement in the physical capacity domain in the QL questionnaire Short Form 36 (QLQ-SF36) in PTG; and significant increase of MIP, WD in the CRET, decrease of systolic arterial pressure and of blood lactate and improvement of total score of QLQ-SF36 in RMT+PTG. Those findings suggest that the PT associated with RMT seems to be the best alternative among the programs investigated in the present study because as well as providing an evident improvement of exercise capacity and of QL in the patients, it provided an additional effect in the physiological adaptation with better effectiveness in the clearance and/or less production of blood lactate during exercise.